Culture of Grass Carp Ctenopharyngodon idella Val. in Fadak farm –Basrah / Iraq - saleh, Jassim H.; Al-Mukhtar, Mustafa A.; Hsooni, Khaled H. (Iraqi Journal of Aquaculture, 2022)
32 thousands of juveniles of grass carp Ctenopharyngodon idella were reared in Fadak fish farm of about 15 g. They were transferred from fish culture station in Marine Science Center and spread equally in four ponds each of 8.5 donum. The culture density was 940 fish /donum in the period 15/ May to 15/ December 2007. Total fish weight for the nearest milligram was taken monthly. Fishes were fed daily with the green alfalfa as a main food item in a rate of 8-15% of the body weight and aquatic plants as Pharagmites australis and Ceratophyllum demersum. Results at the end of experiment show that the average of total weight for each fish in the four ponds reached 1153.79 ± 4.78 gm while the daily weight increase rate varied along the months of experiment from May until December, where it noticed starting from half of June until half August where it reached 1.5± 0.221 gm/day, 4.6 ± 0.712 gm/day and 7.6 ± 0.312 gm / day respectively then it starts to decrease during September until December Relative growth rates show a progressive during the first seven months. On the other hand he specific growth rate showed its highest rates during July (4.6 ± 0.081 %/day).